Identifying and addressing roundabout accessibility issues confronting persons with vision loss in Canada: a pilot study - Adeniran, Omotunde (My University, 2023)
Municipalities and Transportation Agencies in Canada are building more roundabout intersections to promote efficient and safe movement of traffic for their low carbon footprint, low lifetime maintenance cost, and better safety performance thereby reducing collision frequency and severity, among other benefits. The main disadvantage is that Persons with Vision Loss (PWVL) feel unsafe when crossing the street on roundabouts. One of the objectives of this research project is to identify the concerns and challenges experienced by PWVL on roundabouts in Canada through a workshop and opinion surveys involving participants scattered across the country. Another objective is to conduct a field study assessing if the installation of sound strips on the road could help PWVL when deciding to cross the streets on the roundabout in Thunder Bay. To achieve these objectives the research team collaborated with the City of Thunder Bay, the staff, and clients of the Canadian National Institute for the Blind (CNIB) to plan and facilitate various events. It should be mentioned that 3D models of roundabout were used in training and to illustrate points relevant to roundabout accessibility when discussing with PWVL and other stakeholders. [...]
Keywords: Roundabout intersections; Roundabouts (challenges to pedestrians); Unsignalized crosswalks; Roundabout issues & challenges (People with vision loss)